Tourism and climate change in Mauritius: assessing the adaptation and mitigation plans and prospects. Issue 2 (8th April 2019) - Mahadew, Roopanand; Appadoo, Krishnee Adnarain
Abstract : Purpose: The purpose of this paper is to assess the extent to which Mauritius has structured its adaptation to and mitigation of the climate change and its effects on the tourism industry based on the UNEP framework on tourism and climate change. Design/methodology/approach: The UNEP framework is used as a guideline based on which an assessment of the various policies, laws or regulations existent in Mauritius is carried out. Findings: The paper highlights the significant lacunas that exist in Mauritius with regard to this subject matter with measures taken in good faith but not structured and oriented enough to meet long-term goals. Originality/value: This paper adds to the meagre literature that exists in Mauritius on the legal or normative framework that exists in Mauritius concerning climate change and the tourism industry.